1993
DOI: 10.1111/j.1365-2958.1993.tb01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of two ScrR repressors and of a ScrR–FruR hybrid repressor for sucrose and D‐fructose specific regulons from enteric bacteria

Abstract: The scr regulon of pUR400 and the chromosomally encoded scr regulon of Klebsiella pneumoniae KAY2026 are both negatively controlled by a specific repressor (ScrR). As deduced from the nucleotide sequences, both scrR genes encode polypeptides of 334 residues (85.5% identical base pairs, 91.3% identical amino acids), containing an N-terminal helix-turn-helix motif. Comparison with other regulatory proteins revealed 30.6% identical amino acids to FruR, 27.0% to Lacl and 28.1% to GalR. Six scrRs super-repressor mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…Hydrolysis of sucrose 6-phosphate by S6PH yields G6P and fructose, and for K. pneumoniae, fructose is believed to be the inducer of the scr operon (Jahreis & Lengeler, 1993). Hydrolysis of the phosphorylated isomers by AglB of K. pneumoniae also yields G6P and fructose, and formation of the latter ketohexose is consistent with the high levels of S6PH and FK present in cells grown on the isomers (Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…Hydrolysis of sucrose 6-phosphate by S6PH yields G6P and fructose, and for K. pneumoniae, fructose is believed to be the inducer of the scr operon (Jahreis & Lengeler, 1993). Hydrolysis of the phosphorylated isomers by AglB of K. pneumoniae also yields G6P and fructose, and formation of the latter ketohexose is consistent with the high levels of S6PH and FK present in cells grown on the isomers (Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…The genes mediating sucrose uptake and hydrolysis are usually clustered on the chromosome and form operons or regulons (2,4,7,8,13,21,31,35,37) (GenBank accession number L32093). Regulation of the sucrose utilization system is best studied in Bacillus subtilis, in which positive control involves a transcriptional antitermination mechanism (1,11,22).…”
mentioning
confidence: 99%
“…Regulation of the sucrose utilization system is best studied in Bacillus subtilis, in which positive control involves a transcriptional antitermination mechanism (1,11,22). In a number of gram-negative bacteria, repressor proteins of the GalR-LacI family negatively control the expression of the sucrose genes (3,4,8,21). Since several gram-positive bacteria carry homologous putative regulatory genes close to the sucrose gene clusters (31) (GenBank accession numbers L32093 and M36849), they may employ a similar negative regulation mechanism.…”
mentioning
confidence: 99%
“…Gel mobility shift assays with the 300-bp DNA fragment preceding scrY and the repressor showed that ScrR binds to this region and that fructose and not sucrose is the molecular inducer of scrYAB transcription, as in pUR400 and K. pneumoniae. The scr repressors of pUR400 and K. pneumoniae interact with a helix-turn-helix with the operator palindrome TAAACC/GGTTTA preceding scrY and scrK and bind to fructose or fructose 1-phosphate but not to sucrose (34). A part of this sequence (AACC/GGTT) was found in front of scrY and is possibly the operator in the scr regulon of E. amylovora.…”
Section: Discussionmentioning
confidence: 99%
“…The scr regulons of K. pneumoniae and pUR400 consist of four structural genes: scrK codes for an ATP-dependent fructokinase (5), scrY codes for a sucrose-specific porin of the outer membrane (30), scrA codes for enzyme II scr of the PTS, and scrB codes for an intracellular ␤-D-fructofuranoside fructohydrolase (EC 3.2.1.26), which cleaves sucrose 6-phosphate into ␤-D-fructose and ␣-D-glucose 6-phosphate (51). The regulon is controlled by the negative regulator ScrR (34) and is induced in medium containing sucrose, fructose, or raffinose (45,46).…”
mentioning
confidence: 99%